The influence of work environment on employee performance at Ranhill SAJ Sdn Bhd / Nor Akashah Rusli - Rusli, Nor Akashah (Faculty of Business and Management, 2019)
Nowadays, employee performance has always been the most important issue which concerns the managers in every organization. Furthermore, for every organization employee performance are the roots that helps them to succeed in various ways. Therefore, it is the responsibility of the organization itself in observing carefully on the aspects or grounds for the employees to excel. The purpose of this study was to identify the relationship between physical environment, communication and supervisor support towards employee performance. Furthermore, this study was also to identify the most dominant factor which contributes to employee performance. The primary data has been collected from employees of Ranhill SAJ Sdn Bhd through questionnaire. To test the hypothesis, SPSS 22.0 has been adopted for basic analysis purposes. The result showed that all the independent variables (physical environment, communication and supervisor support) have a significant relationship between dependent variable (employee performance). Form the result, the most dominant factor that contributes towards employee performance is physical environment. Overall, it can be concluded that all the research objectives, questions as well as hypothesis in this study has been truly answered.